2021
DOI: 10.3390/nu13051514
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Level of Adherence to Mediterranean Diet on the Parameters of Metabolic Syndrome: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: High adherence to the Mediterranean diet (MD) has been associated with a lower prevalence of Metabolic Syndrome (MetS). The present study aimed to investigate the impact of MD adherence on parameters of MetS. A systematic literature search was performed in PubMed, Cochrane Central Registry of Clinical Trials (CENTRAL), Scopus, EMBASE, Web of Science and Google Scholar databases. Observational studies that recorded adherence to MD and components/measures of the MetS, such as waist circumference (WC), blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 142 publications
(282 reference statements)
6
28
0
Order By: Relevance
“…The authors reported the beneficial effects of a higher MD adherence on both HDL-c and TG levels, the latter coinciding with more frequent olive oil intake, the main denominator of the MD. Results on HDL-c were in agreement with a cross-sectional study [ 7 ] and an intervention study [ 6 ] on healthy volunteers also included in the issue [ 6 ], and results on HDL-c and TG are in agreement with the systematic review published on metabolic syndrome specific risk factors [ 1 ]. The authors found that nutritional counselling improved adherence, as was also suggested by Grabia and colleagues in their study on T1DM women [ 2 ].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The authors reported the beneficial effects of a higher MD adherence on both HDL-c and TG levels, the latter coinciding with more frequent olive oil intake, the main denominator of the MD. Results on HDL-c were in agreement with a cross-sectional study [ 7 ] and an intervention study [ 6 ] on healthy volunteers also included in the issue [ 6 ], and results on HDL-c and TG are in agreement with the systematic review published on metabolic syndrome specific risk factors [ 1 ]. The authors found that nutritional counselling improved adherence, as was also suggested by Grabia and colleagues in their study on T1DM women [ 2 ].…”
supporting
confidence: 87%
“…If present trends persist, it is expected that non-communicable diseases (NCD) will have a growing incidence, making the studies included in the present Special Issue (SI) imperative, since despite the first ecological and population-based data, the aspects of the MD that may promote health in respect to other lifestyle variables remain under investigation, as Balakoudi and colleagues concluded following a systematic review [ 1 ]. This SI contains multifaceted research articles and a systematic review, which have addressed these issues both in healthy individuals and in those with specifically defined disease states or risk factors.…”
mentioning
confidence: 99%
“…A non-Mediterranean pattern, with the intake of unhealthy foods, increases the risk of inflammatory and oxidative stress linked with cardiovascular diseases, obesity and cancer [ 42 ]. A systematic review of 41 observational studies revealed that high adherence to the Mediterranean diet is associated with an improvement in all parameters of metabolic syndrome in adults [ 43 ]. The present study shows that a large proportion of university students had low adherence to the Mediterranean diet.…”
Section: Discussionmentioning
confidence: 99%
“…21 MedD has been shown to be effective in reducing cardiovascular mortality, in controlling arterial hypertension, in preventing obesity and metabolic syndrome. 22,23 A systematic review that analyzed data from 7186 subjects reported a significant reduction in visceral obesity on a Mediterranean or similar diet. 24 The Mediterranean diet is rich in fruit and vegetables and is naturally low in sodium due to its low degree of processing foods.…”
Section: Lifestyle and Risk Factorsmentioning
confidence: 99%
“…MedD has been shown to be effective in reducing cardiovascular mortality, in controlling arterial hypertension, in preventing obesity and metabolic syndrome. 22 , 23 …”
Section: Primary Prevention Of Cardiovascular Diseasementioning
confidence: 99%